Interpretation of Ḍamīr Huwa in the Tafsir of Isyārī Surah Al-Ikhlāṣ and Its Relevance in Contemporary Spirituality Discourse - Djuned, Muslim; Harizi, Hasvi; Misnawati; Jannah, Nur (QOF, 2025)
This study examines the interpretation of the ḍamīr huwa in the isyārī interpretation of Sūrat al-Ikhlāṣ, focusing on the dimension of tawḥīd and its relevance to contemporary spiritual discourse. Employing a qualitative, textual analysis approach, this study analyzes the works of Sufi mufassirs such as Ibn ʿAjībah, Imām al-Ālūsī, and Muḥammad al-Bayṭār. It also addresses the polemic between the Majelis Pengkajian Tauhid Tasawuf Indonesia (MPTT-I) and the Majelis Ulama Indonesia (MUI) concerning the interpretation of ḍamīr huwa in Sūrat al-Ikhlāṣ. The findings indicated that huwa is not merely a pronoun referring to Allah but also a symbol of the highest level of spiritual consciousness. Within the context of modern spirituality, this understanding resonates with the concept of mindfulness, wherein awareness of God’s presence becomes a source of inner tranquility. Furthermore, this interpretation may foster tolerance, as it emphasizes that God transcends the boundaries of religious formalism. In the context of exegetical polemics, MPTT-I understands huwa as an implicit (ghaybī) pronoun associated with the concept of al-Insān al-Kāmil and referring to the Prophet Muḥammad. In contrast, MUI asserts that huwa must be unequivocally referred to Allah. This study underscores the importance of adopting a moderate approach to isyārī interpretation to enrich spiritual understanding and prevent theological conflict. Further research is recommended to explore more deeply the roots of this polemic and the epistemological limitations of isyārī exegesis in contemporary Islamic discourse.